1997
DOI: 10.1182/blood.v89.5.1543
|View full text |Cite
|
Sign up to set email alerts
|

Mouse Strain-Dependent Changes in Frequency and Proliferation of Hematopoietic Stem Cells During Aging: Correlation Between Lifespan and Cycling Activity

Abstract: We have quantified the frequency and proliferation of five subsets of primitive hematopoietic cells, using the cobblestone area forming cell (CAFC) assay, in marrow of five strains of mice with lifespans ranging from about 500 to 800 days. Stem cell characteristics were determined in young (6 weeks) and old (12 months) mice. We report striking effects of both intrinsic strain lifespan and individual mouse age on stem cell populations. First, the relative and absolute numbers of the most primitive stem cell sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 257 publications
(54 citation statements)
references
References 32 publications
2
52
0
Order By: Relevance
“…The increase in the frequency of CFU-GM in the bone marrow as a function of age may seem surprising at ®rst sight. However, a similar age-related increase in the frequency of clonogenic cells has also been found in mice (Morrison et al, 1996;de Haan et al, 1997). This increase could be accounted for by a reduced level of mature cell production which, in turn, might indicate a progressive functional de®ciency of the progenitor cells themselves.…”
Section: Discussionmentioning
confidence: 52%
“…The increase in the frequency of CFU-GM in the bone marrow as a function of age may seem surprising at ®rst sight. However, a similar age-related increase in the frequency of clonogenic cells has also been found in mice (Morrison et al, 1996;de Haan et al, 1997). This increase could be accounted for by a reduced level of mature cell production which, in turn, might indicate a progressive functional de®ciency of the progenitor cells themselves.…”
Section: Discussionmentioning
confidence: 52%
“…Additionally, experimental data indicate, e.g., that the age‐dependent development of HSC activity is highly strain specific. Whereas in some mouse strains the cycling activity of HSC has been reported to decrease with age (e.g., DBA mice), in others strains this effect is not detectable (e.g., B6 mice) (De Haan et al. , 1997; De Haan & Zant, 1999).…”
Section: Introductionmentioning
confidence: 98%
“…Significant progress has been made during the last decade in developing culture systems to study the differentiation of human CD34 cells intto enucleate reticulocytes and using various cell surface markers to monitor the progression through all stages of erythroid differentiation. [4][5][6][7] These developments are enabling detailed characterization of normal and disordered human erythropoiesis. [8][9][10][11][12][13] Importantly, as a result of this progress it is now possible to obtain insights into at what stage of the complex process of erythroid differentiation various genes contribute to ineffective erythropoiesis.…”
Section: Staying Hydrated Is Important Also For Erythroblastsmentioning
confidence: 99%
“…Phenotypic diversity is frequently caused by genetic variations such as single nucleotide polymorphism (SNP). It was reported that the size and function of the HSC pool vary between mice strains, [5][6][7][8][9] which suggests genetic background, such as SNP and copy number variations, define HSC homeostasis. In 2007, Liang et al identified latexin (Lxn) as an HSC regulatory gene whose expression level is inversely correlated with HSC number.…”
mentioning
confidence: 99%